Balanced Scorecard Application - Lorenc, Igor; Neumaierová, Inka, 1960-; Kodejšová, Tereza; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The Master’s thesis is focused on the application of the strategic planning and management system Balanced Scorecard in Sberbank CZ – banking institution offering complex financial services on the Czech market. The first part of the thesis provides the theoretical basis for application of the method, basics of strategic analysis and frameworks and tools used in the analysis. The practical part constitutes of introduction, external analysis, internal analysis, and SWOT analysis of the company. Subsequently, the strategic goals, metrics and actions are developed for each of the perspectives of the Balanced Scorecard. Finally, the logical interconnections between the perspectives are displayed in the strategy map.
Vedoucí práce: Inka Neumaierová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses